PROCESY UPADŁOŚCIOWE BANKÓW KOMERCYJNYCH NA TLE EWOLUCJI SEKTORA BANKOWEGO W LATACH 1989 - 2001 - Appenzeller, Dorota; Nowara, Wanda (Wydział Prawa i Administracji UAM, 2002)
The article gives an account of the evolving Polish banking sector after 1989 with a special focus on bankruptcy proceedings and taking over troubled banks by other financial institutions. The account is complemented with an analysis of the change dynamics and financial conditions of commercial banks in 1992 and 2001. The main goal of the analysis was to determine whether there are any common features of the banks that either became insolvent or were taken over following their financial problems.
COMMERCIAL BANK BANKRUPTCY PROCEEDINGS AGAINST THE BACKGROUND OF BANKING EVOLUTION BETWEEN 1989 AND 2001